The Dual-Position Polemic: Questioning The Normalization Of Legal Regulation Violations Amid Efforts To Achieve Good Governance - Tarigan, Chandra; Azrianti, Seftia; Rabu, Rabu (PPPM, Sekolah Tinggi Ilmu Hukum (STIH) Biak-Papua, 2026)
The practice of holding multiple positions (concurrent posts) in Indonesia has become a habit and is often regarded as something normal and acceptable. Every government regime, from time to time, continues to engage in this practice, which has even become more widespread. In fact, several laws and regulations clearly prohibit and restrict such practices. However, it must be acknowledged that existing loopholes in legal regulations are often used as justifications to legitimize the practice of holding multiple positions.This study seeks to describe the increasingly widespread phenomenon of concurrent office-holding in Indonesia and its impact on the ideals of realizing good governance, using a normative juridical method. The government should take a firm and decisive stance regarding this matter, as the practice of holding multiple positions has a tangible negative impact, particularly on the implementation of effective, corruption-free, and good governance.